Polling in New Democracies and Electoral Malpractice: The Case of Brazil. (22nd May 2021) - Lloyd, Ryan; Turgeon, Mathieu
Abstract: In many developing democracies, polling often comes with elevated levels of bias and variance. We argue that electoral malpractice can be one reason why. We build a theory and test it with data from elections between 2002 and 2014 in Brazil. We find that polling errors are larger in: (a) elections with many undecided voters and large imbalances in financial resources among campaigns; (b) the poorer Northeast region of Brazil, which is more closely associated with patronage and vote buying; and (c) low-profile, low-information elections. Our analysis serves as a cautionary tale for interpreting polling in democracies like Brazil, even if/when other sources of error in the polling industry are mitigated.